PENGARUH KURS RUPIAH, INFLASI,BI RATE, FED RATE, DAN SHANGHAI STOCK EXCHANGE COMPOSITE (SSEC) TERHADAP INDEKS HARGA SAHAM SEKTOR PROPERTI, REAL ESTAT, DAN KONSTRUKSI BANGUNAN (Studi Kasus pada Bursa Efek IndonesiaPeriode 2014-2018) - Arthit Jayanti Hardiman; Sri Widiyati Widiyati; Moch. Abdul Kodir (Politeknik Negeri Semarang, 2019)
This research aims to analyze the influence of the rupiah exchange rate, inflation, BI rate, FED rate, and SSEC onThe Stock Price Index of Property, Real Estate and Building Constructionon Indonesia Stock Exchange during 2014-2018. This research used secondary data. The sampling methodused total sampling, so the sample is the entire population or all of companies listed in property, real estate, and building construction sector on Indonesia Stock Exchange during 2014-2018. The research statistical model used multiple linear regression analysis model processed by software SPSS 25. The equation of this regression model estimation on this research: IHSSP = 339.651 – 0.019KU -837.814IN + 460.140BR + 141.072FR + 0.023IS + ℯ. The F testresult of this research show the rupiah exchange rate, inflation, the BI rate, the FED rate, and SSEChave significant simultaneously influence on the Sector Stock Price Index of Property, Real Estate, and Building Construction. Then the t test result of this research show the rupiah exchange rate has significant partially influence, so H1 was accepted. Inflation has significant partially influence, so H2 was accepted. BI rate has not significant partially influence, so that H3 was rejected. FED rate has not significant partially influence, so H4 was rejected. SSEC has significant partially influence, so H5 was accepted on the Sector Stock Price Index of Property, Real Estate, and Building Construction. The coefficient of determination is 0.826., so the ability variation of the independent variables (rupiah exchange rate, inflation, BI rate, FED rate, and SSEC) in explaining the variation of the dependent variable (Sector Stock Price Index of Property, Real Estate, and Building Construction) was 82.6%, while the rest was explained by other independet variable soutside this research